2016
DOI: 10.18632/oncotarget.9332
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a WNT5A-IL-6 positive feedback loop in melanoma cells: Dual interference of this loop more effectively impairs melanoma cell invasion

Abstract: Increased expression and signalling of WNT5A and interleukin-6 (IL-6) have both been shown to promote melanoma progression. Here, we investigated the proposed existence of a WNT5A-IL-6 positive feedback loop that drives melanoma migration and invasion. First, the HOPP algorithm revealed that the invasive phenotype of cultured melanoma cells was significantly correlated with increased expression of WNT5A or IL-6. In three invasive melanoma cell lines, endogenous WNT5A protein expression was related to IL-6 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…We have previously reported the existence of an IL‐6/WNT5A positive feedback loop in parental BRAFi‐sensitive melanoma cells that is related to their migratory and invasive properties (Linnskog et al ., ). The above findings of a parallel increase in WNT5A expression and IL‐6 secretion are in good agreement with such an IL‐6/WNT5A feedback loop also in BRAFi‐R melanoma cells.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously reported the existence of an IL‐6/WNT5A positive feedback loop in parental BRAFi‐sensitive melanoma cells that is related to their migratory and invasive properties (Linnskog et al ., ). The above findings of a parallel increase in WNT5A expression and IL‐6 secretion are in good agreement with such an IL‐6/WNT5A feedback loop also in BRAFi‐R melanoma cells.…”
Section: Resultsmentioning
confidence: 97%
“…Our observation of elevated IL‐6 secretion is in accordance with the observation that IL‐6 is not only a promoter of melanoma metastasis (Na et al ., ) but also an inducer of WNT5A protein expression in parental BRAFi‐sensitive melanoma cells (Linnskog et al ., ). Furthermore, an IL‐6/WNT5A positive feedback loop has been previously shown to be associated with the increased invasive migration of parental BRAFi‐sensitive melanoma cells (Linnskog et al ., ). However, in contrast to this latter finding, we found that the IL‐6/WNT5A positive feedback loop is absent in BRAFi‐R melanoma cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In mice, IL-6 regulates gut epithelial crypt homeostasis through the Wnt signalling pathway [41]. In humans, there is a positive feedback loop between IL-6 and WNT5A in melanoma cells [42], and WNT5A-FZD4/LRP5 signaling support self-renewal of embryonic stem cells [43] and eMSCs [9].…”
Section: Discussionmentioning
confidence: 99%
“…WNT5A modulates melanoma cell behavior via multiple cell surface receptors/co-receptors, including ROR2 [9] and Frizzleds [10], and downstream molecular targets, such as APT1 [11], IL-6 [12], and PKC-STAT3 [13], which in turn affect various melanoma cell functions, including migration and invasion. One clear example of the essential role of WNT5A signaling in melanoma cell dissemination is the observation that simultaneous inhibition of WNT5A expression (with an anti-IL-6 antibody) and downstream WNT5A signaling (with the WNT5A antagonistic peptide Box5) effectively impairs melanoma cell migration and invasion [12]. An important pathway that has been shown to be crucial for WNT5A-mediated melanoma invasion and metastasis is the protein kinase C (PKC) signaling pathway, as demonstrated in several studies by Weeraratna and coworkers [8,9,14].…”
Section: Introductionmentioning
confidence: 99%